Lithium preserves peritoneal membrane integrity by suppressing mesothelial cell αB-crystallin - Herzog, Rebecca; Sacnun, Juan Manuel; Gonzalez-Mateo, Guadalupe; Bartosova, Maria; Bialas, Katarzyna; Wagner, Anja; Unterwurzacher, Markus; Sobieszek, Isabel J.; Daniel-Fischer, Lisa; Rusai, Krisztina; Pascual-Anton, Lucia; Kaczirek, Klaus; et al. (Science translational medicine, 2021)
Life-saving renal replacement therapy by peritoneal dialysis (PD) is limited in use and duration by progressive impairment of peritoneal membrane integrity and homeostasis. Preservation of peritoneal membrane integrity during chronic PD remains an urgent but long unmet medical need. PD therapy failure results from peritoneal fibrosis and angiogenesis caused by hypertonic PD fluid (PDF)-induced mesothelial cytotoxicity. However, the pathophysiological mechanisms involved are incompletely understood, limiting identification of therapeutic targets. We report that addition of lithium chloride (LiCl) to PDF is a translatable intervention to counteract PDF-induced mesothelial cell death, peritoneal membrane fibrosis, and angiogenesis. LiCl improved mesothelial cell survival in a dose-dependent manner. Combined transcriptomic and proteomic characterization of icodextrin-based PDF-induced mesothelial cell injury identified alpha B-crystallin as the mesothelial cell protein most consistently counter-regulated by LiCl. In vitro and in vivo overexpression of alpha B-crystallin triggered a fibrotic phenotype and PDF-like up-regulation of vascular endothelial growth factor (VEGF), CD31-positive cells, and TGF-beta-independent activation of TGF-beta-regulated targets. In contrast, alpha B-crystallin knockdown decreased VEGF expression and early mesothelial-to-mesenchymal transition. LiCl reduced VEGF release and counteracted fibrosis- and angiogenesis-associated processes. zeta B-crystallin in patient-derived mesothelial cells was specifically up-regulated in response to PDF and increased in peritoneal mesothelial cells from biopsies from pediatric patients undergoing PD, correlating with markers of angiogenesis and fibrosis. LiCl-supplemented PDF promoted morphological preservation of mesothelial cells and the submesothelial zone in a mouse model of chronic PD. Thus, repurposing LiCl as a cytoprotective PDF additive may offer a translatable therapeutic strategy to combat peritoneal membrane deterioration during PD therapy.
Gesehen am 08.12.2021